The N-terminal region is crucial for the thermostability of the G-domain of Bacillus stearothermophilus EF-Tu - Sanderová, Hana; Tiserová, Hana; Barvík, Ivan; Sojka, Ludek; Jonák, Jirí; Krásný, Libor (Biochimica et biophysica acta, 2010)
Bacterial elongation factor Tu (EF-Tu) is a model monomeric G protein composed of three covalently linked domains. Previously, we evaluated the contributions of individual domains to the thermostability of EF-Tu from the thermophilic bacterium Bacillus stearothermophilus. We showed that domain 1 (G-domain) sets up the basal level of thermostability for the whole protein. Here we chose to locate the thermostability determinants distinguishing the thermophilic domain 1 from a mesophilic domain 1. By an approach of systematically swapping protein regions differing between G-domains from mesophilic Bacillus subtilis and thermophilic B. stearothermophilus, we demonstrate that a small portion of the protein, the N-terminal 12 amino acid residues, plays a key role in the thermostability of this domain. We suggest that the thermostabilizing effect of the N-terminal region could be mediated by stabilizing the functionally important effector region. Finally, we demonstrate that the effect of the N-terminal region is significant also for the thermostability of the full-length EF-Tu.
Keywords: Models, Molecular; molekulární modely; Protein Structure, Tertiary; Amino Acid Sequence; sekvence aminokyselin; vysoká teplota; stabilita proteinů; Molecular Sequence Data; elongační faktor Tu; Geobacillus stearothermophilus; Hot Temperature; Bacillus subtilis; Peptide Elongation Factor Tu; Protein Stability; molekulární sekvence - údaje; terciární struktura proteinů